Full-Scale Assessment of Seismic and Wind Load Performance in the Design of a Flexible Solar-Shading Double-Skin Façade - José Pérez-Fenoy; Carlos Rivera-Gómez; Jorge Roa-Fernández; Carmen Galán-Marín (Buildings, 2023)
Cable-supported façades represent a novel approach in the design and technology of double skin façades (DSFs). This type of system not only offers flexibility in terms of exterior finishes, but also regulates the access of solar radiation, thereby transforming the appearance of the building in response to varying daylight conditions. However, the structural performance of these façades under wind, impact, and seismic loads remains an active area of research. The study is a groundbreaking work that experimentally evaluates the wind and seismic behaviour of these type of façades. The methodology used for the evaluation of flexible masonry facades includes laboratory tests analysing the individual capacity of the connections and materials of the system under standardized and non-standardized procedures. A full-scale experimental sub-assembly specimen of a representative module of the façade is also subjected to uniformly distributed pressures of wind load tests, as well as hard body and soft body impact tests. The setup considered the border conditions, tension loads, and actual materials. Furthermore, the earthquake assessment includes tests of full-scale specimens subjected to these demands. The results show up to 30% enhanced performance relative to similar systems reported in the literature. Furthermore, research findings facilitated the refinement and redesign of the system components, thereby validating the DSF case study.